Functions of Nonverbal Behavior with Reference to Refugeeism: A Sociopragmatic Study - Mahmood, Rauf Karim; Hussein, Bekhal Abubakir (Sulaimani Journal for Humanities, 2019)
This paper is an extract from a Ph.D. dissertation entitled “A Sociopragmatic Analysis of Nonverbals in Intercultural Communication: A Case Study of Refugees in Kurdistan Region.” Nonverbal communication is universally important to enhance better human understanding and cooperation. It has been widely proved that interpretation and comprehension of this type of communication are crucial among diverse nations, cultures, and ethnic groups, in particular. Nowadays, refugeeism has become a global phenomenon, and the refugee number has risen due to armed political conflicts in Middle-Eastern countries. Kurdistan region is one of the critical areas that have a long history with refugeeism. Kurdish people have become refugees; on the one hand, the Kurdistan region has become a haven for refugees and IDPs of the neighboring areas, on the other hand. Refugees face lots of political, economic, social and psychological problems. Also, difficulties in verbal and nonverbal communication increase their suffering. Thus, the demand for communication reinforcement has become essential and urgent to treat refugees with better nonverbal communication strategies. This paper attempts to explain the functions of nonverbal cues in sociopragmatic refugeeism context. The paper initiates by outlining some definitions of sociopragmatics, nonverbal communication, and it goes on to explain the communicative functions of nonverbal cues. Examples displayed here are from real refugee camps in Sulaimani Governorate, Kurdistan Region of Iraq. The paper finds out that the sociopragmatic refugee context has an outstanding impact on the usage of specific nonverbal cues and their functions.
Keywords: Sociopragmatics; Nonverbal Communication; Nonverbal Behavior Functions; Refugeeism